2019
DOI: 10.3174/ajnr.a6099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple Sclerosis Cortical Lesion Types Detected by Multicontrast 3T and 7T MRI

Abstract: BACKGROUND AND PURPOSE: Our aims were the following: 1) to compare multicontrast cortical lesion detection using 3T and 7T MR imaging, 2) to compare cortical lesion type frequency in relapsing-remitting and secondary-progressive MS, and 3) to assess whether detectability is related to the magnetization transfer ratio, an imaging marker sensitive to myelin content. MATERIALS AND METHODS: Multicontrast 3T and 7T MR images from 10 participants with relapsing-remitting MS and 10 with secondaryprogressive MS. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“… 82 These results were confirmed in a recent study including 20 MS patients. 83 A postmortem study in brain sections of 19 MS patients using T1w, T2w, T2-FLAIR, DIR, or T2*w further substantiated this finding. 14 Of note, this study found a similarly low sensitivity of 7% to detect subpial lesions for DIR both at 3 and 7 T. Results from 1 study suggested that 7-T T2-FLAIR shows higher sensitivity at detecting cortical lesions compared with DIR, T2w, or T1w images.…”
Section: Magnetic Resonance Imaging At 7 Tmentioning
confidence: 84%
“… 82 These results were confirmed in a recent study including 20 MS patients. 83 A postmortem study in brain sections of 19 MS patients using T1w, T2w, T2-FLAIR, DIR, or T2*w further substantiated this finding. 14 Of note, this study found a similarly low sensitivity of 7% to detect subpial lesions for DIR both at 3 and 7 T. Results from 1 study suggested that 7-T T2-FLAIR shows higher sensitivity at detecting cortical lesions compared with DIR, T2w, or T1w images.…”
Section: Magnetic Resonance Imaging At 7 Tmentioning
confidence: 84%
“…Due to an increased spatial resolution and better tissue contrast, 7-T MRI has allowed a more accurate detection and characterisation of cortical GM lesions [28][29][30][31][32][33]. Cortical lesions are very common at histopathological examination, especially in the progressive forms of MS [34].…”
Section: Cortical Lesions and Cortical Pathologymentioning
confidence: 99%
“…Moreover, cortical lesions are associated with disability progression [ 36 ] and cognitive impairment and could thus represent an important biomarker in the evaluation of progression of disease burden in MS. Focal cortical lesions are poorly visualised using conventional MRI sequences at 1.5 T [ 37 ] and 3 T, because of their small size, lower amount of inflammation than WM lesions, and partial volume effects with CSF. Since the first ex vivo and in vivo applications, it was clear that 7-T MRI improves not only detection of cortical lesions compared to 3-T MRI [ 29 , 30 , 38 ], but it also improves lesion localisation and classification [ 28 , 30 ]. A recent study by Treaba et al [ 32 ] found that cortical lesions predominantly develop intracortically and within sulci, supporting an inflammatory cerebrospinal fluid-mediated lesion pathogenesis of those lesions, as already suggested by MRI-pathological correlation studies [ 39 , 40 ] (Fig.…”
Section: Ms Lesion Analysismentioning
confidence: 99%
“…Other contrasts have been tested and optimized at 7T [6][7][8] to identify sequenced with the highest value for detecting CL in clinic. The comparison of T2 * contrast at 7T with 3T double inversion recovery 9 sequence or multicontrast data 10 that are more accessible in clinic demonstrated the superiority of the T2 * -sequence at 7T in detecting intracortical, especially subpial, lesions. Despite this, leukocortical lesion identification at 7T remains similar to that achieved at 3T 10 .…”
Section: Cortex -Cortical Lesion Detectionmentioning
confidence: 99%
“…The comparison of T2 * contrast at 7T with 3T double inversion recovery 9 sequence or multicontrast data 10 that are more accessible in clinic demonstrated the superiority of the T2 * -sequence at 7T in detecting intracortical, especially subpial, lesions. Despite this, leukocortical lesion identification at 7T remains similar to that achieved at 3T 10 . The sensitivity of CL detection, however, cannot be inferred from imaging alone without histopathology validation.…”
Section: Cortex -Cortical Lesion Detectionmentioning
confidence: 99%